DUKUNGAN ORGANISASI YANG DIRASAKAN DAN KETERIKATAN KARYAWAN PADA KARYAWAN PT. BANK RAKYAT INDONESIA (Persero) Tbk, CABANG BANDA ACEH - Julita, Santi; Andriani, Iin (Jurnal Psikologi, 2017)
Development of globalization impact to a strict competition between the companies. This lead the Human Resources factor into a crucial role in maintaining, directing and developing the company. Therefore, every company needs employees who are bound by their job. One of the things that can encourage the formation of relationship between the employee is perceived organizational support. This study aims to determine the relationship between perceived organizational support by attachment of employees at PT. Bank Rakyat Indonesia (Persero) Tbk, Branch of Banda Aceh. The number of samples in this study were 139 permanent employees who were still working or were not taking time off from work with a minimum term of one year and the last education was diploma. The sampling technique used purposive sampling technique. Collecting the data using the scale adaptation of Survey of Perceived Organizational Support with 17-item version (Î±= .91) and a scale adaptation of Utrecht Work Engagement Scale (UWES) with 17-item version (Î±= .95). The results of data analysis using pearson product moment correlation technique that showed a positive relationship between perceived organizational support by attachment of employees at PT. Bank Rakyat Indonesia (Persero) Tbk, Branch of Banda Aceh (rxy = .30, p < .05). The higher of perceived organizational support to the employee, likewise the higher bound of employee or otherwise.Â